2017
DOI: 10.1186/s12933-016-0493-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, active- and placebo-controlled, three-period crossover trial to investigate short-term effects of the dipeptidyl peptidase-4 inhibitor linagliptin on macro- and microvascular endothelial function in type 2 diabetes

Abstract: BackgroundStudies of dipeptidyl peptidase (DPP)-4 inhibitors report heterogeneous effects on endothelial function in patients with type 2 diabetes (T2D). This study assessed the effects of the DPP-4 inhibitor linagliptin versus the sulphonylurea glimepiride and placebo on measures of macro- and microvascular endothelial function in patients with T2D who represented a primary cardiovascular disease prevention population.MethodsThis crossover study randomised T2D patients (n = 42) with glycated haemoglobin (HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…The glomerular hyperfiltration that characterizes early diabetic nephropathy is associated with increased basal nitric oxide activity [154,155]. Another mechanistic, randomized clinical study found that 4 weeks of linagliptin treatment improved microvascular endothelial function compared with both placebo and the sulphonylurea, glimepiride [156]. In this crossover study in 42 patients with early type 2 diabetes, there was no significant change in macrovascular endothelial function measured by brachial flow-mediated vasodilation.…”
Section: Elephant In the Room: Clinical Kidney Protection With Dpp-4 mentioning
confidence: 93%
See 1 more Smart Citation
“…The glomerular hyperfiltration that characterizes early diabetic nephropathy is associated with increased basal nitric oxide activity [154,155]. Another mechanistic, randomized clinical study found that 4 weeks of linagliptin treatment improved microvascular endothelial function compared with both placebo and the sulphonylurea, glimepiride [156]. In this crossover study in 42 patients with early type 2 diabetes, there was no significant change in macrovascular endothelial function measured by brachial flow-mediated vasodilation.…”
Section: Elephant In the Room: Clinical Kidney Protection With Dpp-4 mentioning
confidence: 93%
“…In this crossover study in 42 patients with early type 2 diabetes, there was no significant change in macrovascular endothelial function measured by brachial flow-mediated vasodilation. However, there were significant improvements in fasting microvascular function, as measured by changes in blood flow on the dorsal thenar site of the right hand recorded with laser-Doppler flowmetry [156].…”
Section: Elephant In the Room: Clinical Kidney Protection With Dpp-4 mentioning
confidence: 94%
“…In clinical studies, the initial combination of linagliptin and metformin substantially enhanced glycemic control without weight gain and with infrequent hypoglycemia [ 43 ] and also significantly improved microvascular function in the fasting state [ 44 ]. Besides, the special issues of linagliptin is about neuroprotective effects based on some evidences showing that patients treated with linagliptin were significantly associated with fewer events of stroke [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DPP-4 inhibitor-treated type 2 diabetic patients had lower risks for cardiovascular disease as compared to those for non-DPP-4 inhibitor users, except metformin users [ 36 ], and its use did not increase the risk of heart failure compared with sulfonylurea [ 37 ]. The initial combination of linagliptin and metformin substantially improved glycemic control without weight gain and with infrequent hypoglycemia [ 38 ] and also significantly improved microvascular function in the fasting state [ 39 ]. Very importantly, type 2 diabetes is known to significantly accelerate premature aging of systemic organs.…”
Section: Discussionmentioning
confidence: 99%